Pengukuran Getaran Aliran Material Lahar Dingin Memanfaatkan Jaringan Sensor Nirkabel dan Uji Statistik Hasil Percobaan - Agung Priyanto; Landung Sudarmana; Harjono (Politeknosains, 2020)
Lahar events have been major threats following volcano eruptions. The absence of power grid and communication line in remote areas near the volcano, where the lahar events initiate, makes the sensors deployment a difficult thing to do. Sensors, like cameras and other sensing methods, usually can only be deployed in areas where power grid presents, that is, near residential areas, far enough from where lahar event initiates. Thus, the prediction of lahar event takes longer time to make, because of delayed information received by the lahar event mitigation center, and this may be too late. Vibration sensor utilizing an accelerometer integrated with autonomous, power efficient wireless sensor network is a conclusion for the need. The statistical tests for the laboratorium scale experiment results have been made. A validated method of data analysis that has been chosen fits the data pattern. Furthermore, a significant information that can be used as a parameter for the lahar event early warning system can be achieved.